Mediating role of overweight perception in the relationship between healthy eating habits and negative physical health: a multigroup analysis by sex - Cristian Ramos-Vera; Miguel Basauri-Delgado; Christian Casas-Gálvez; Norma Del Carmen Gálvez-Díaz; Jacksaint Saintila; Yaquelin E. Calizaya-Milla (Discover Social Science and Health)
Abstract Background There is limited information on how the perception of being overweight mediates the connection between eating habits and poor physical health in adults. This study aimed to explore how the perception of being overweight mediates the relationship between healthy eating behaviors and negative physical health in adults, with a focus on differences by sex. Methods A cross-sectional study with a predictive approach was conducted using structural equation modeling (SEM). Data were analyzed from 4032 participants (58.16% women and 41.84% men) from the 2019 Health Information National Trends Survey 5 (HINTS-5)-Cycle 3. Results Healthy eating behaviors (EB) were positively associated with the perception of being overweight (PO) in both men (β = 0.127, p < 0.001) and women (β = 0.135, p < 0.001). However, a significant negative direct relationship between EB and negative physical health (NPH) was observed only in women (β = − 0.055, p < 0.001), while this relationship was not significant in men (β = − 0.32, p = 0.098). PO was positively associated with NPH in both sexes (β = 0.628 for men and β = 0.640 for women, p < 0.001 for both). The mediation analysis confirmed that PO mediated the relationship between EB and NPH in both men (β = 0.102, p < 0.001) and women (β = 0.112, p < 0.001), explaining a small but significant portion of the variance in NPH (R2 = 0.020), while the overall model explained a larger portion (R2 = 0.387). Conclusion These findings suggest that incorporating body weight perception into the design of interventions may be beneficial for enhancing physical health through healthy eating behaviors, with particular attention to the differential impact on men and women.